‘‘Communication and Encounter’s Culture’’ in the cultural practice of Akɔmimlan (Fɔn clan’s panegyric) of the Republic of Benin - METIN , Sèdoté Alex Canisius; ALEJO , Albert (Revue Internationale du Chercheur, 2025)
In today’s social context marked by indifference, polarization and extremism, a research about communication practises known for their aptitude to create social cohesion, could help to promote a communication style that facilitates the “encounter’s culture”. Thus motivated, the present research is engaged in studying the communicative characteristics of Akɔmimlan (Fɔn clan’s panegyrics of Benin’s Republic), known for its ability to establish social cohesion. It is carried out through the analysis of five texts and six audio-visuals media, which highlight the words and various performance modes of the practice; as well as ten interviews with members of the social group. The findings reveal that the practice’s specific verbal and non-verbal content, and its particular rhetorical epidictic style based on recognition and valorisation, foster members’ identification and socialization, as well as social group integration. From this analysis, are deduced some communication characteristics, that can promote effective encounters.